Media Sosial Instagram sebagai Media Dakwah - Ulfa Fauzia Zahra; Ahmad Sarbini; Asep Shodiqin (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2016)
This paper discusses the main theme and kategosisasi message da'wah and the meaning of message da'wah in post account islamiposter instagram. The method used is the content analysis of post account Instagram islamiposter account. Of the total 200 posts on the account instagram islamiposter period 1 June 2016 to 30 June 2016 taken as many as 20 post samples are used as data for analysis. The results found there are messages with the category akidah a number of 4 posts, the message with the category of worship 8 postings, and messages with the category of morals 8 posts. Tulisan ini membahas tentang tema pokok dan kategosisasi pesan dakwah serta makna pesan dakwah dalam postingan akun instagram islamiposter. Metode yang digunakan adalah analisis isi terhadap postingan akun Instagram islamiposter. Dari total 200 postingan pada akun instagram Islamiposter periode 1 Juni 2016 hingga 30 Juni 2016 diambil sebanyak 20 sampel postingan yang dijadikan sebagai data untuk dianalisis. Hasil penelitian menemukan terdapat pesan dengan kategori akidah sejumlah 4 postingan, pesan dengan kategori ibadah 8 postingan, dan pesan dengan kategori akhlak 8 postingan.